Chronic calcifying pancreatitis of alcoholic origin: double bypass: cholecyst and wirsungojejunostomy - Delgado, Bolívar (Cirugía del Uruguay, 2020)
This paper presents the conclusions derival from the observation of one case of chronic alcoholic pancreatitis, treated with good results by double derivation; gallbladder and duct of wirsung-jejunum. The treatment given at present to this disease, which is so rare in our media, is discussed.